2023
DOI: 10.1038/s41699-023-00365-5
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared to red-light emission and carrier dynamics in full series multilayer GaTe1−xSex (0≤x≤1) with structural evolution

Abstract: Two-dimensional layered gallium monochalcogenide (GaX, where X = S, Se, Te) semiconductors possess great potential for use in optoelectronic and photonic applications, owing to their direct band edge. In this work, the structural and optical properties of full-series multilayer GaTe1−xSex for x = 0 to x = 1 are examined. The experimental results show that the whole series of GaTe1−xSex layers may contain one hexagonal (H) phase from GaTe to GaSe, whereas the monoclinic (M) phase predominates at 0 ≤ x ≤ 0.4. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 61 publications
6
5
0
Order By: Relevance
“…In the unpolarized measurement configuration, the Raman spectrum of GaTe0.5Se0.5 shows three distinct peaks located at 126, 224, and 301 cm -1 , respectively. The positions of these three peaks align closely with reported in prior literature 36 . The assigned modes correspond to Ag (1) , Eg, and Ag (2) modes, providing an additional confirmation of the material's classification as the 2H phase.…”
Section: Resultssupporting
confidence: 89%
“…In the unpolarized measurement configuration, the Raman spectrum of GaTe0.5Se0.5 shows three distinct peaks located at 126, 224, and 301 cm -1 , respectively. The positions of these three peaks align closely with reported in prior literature 36 . The assigned modes correspond to Ag (1) , Eg, and Ag (2) modes, providing an additional confirmation of the material's classification as the 2H phase.…”
Section: Resultssupporting
confidence: 89%
“…According to prior studies ,, as well as from the crystal morphology, In 6 Se 7 :P has a monoclinic structure with a multiline long-edge outline along the b axis. Similar to the other monoclinic structures in the III–VI semiconductors, such as GaTe , and M-GaTe 1– x Se x , the multiline edges are elongated in the b ( y ) axis.…”
Section: Resultssupporting
confidence: 52%
“…III–VI layered semiconductors have gained significant attention due to their unique electronic and optical properties as well as specific technological applications. , The III and VI monochalcogenides possess a general chemical formula of MX, where M is a group III element (such as Ga or In), and X is a chalcogen atom (such as Te, Se, or S). One of the most exciting properties of III–VI layered semiconductors is their direct band edge constructed in the multilayer form, this can make them an ideal candidate for various optoelectronics applications such as solar cells, photodetectors, and light-emitting diodes. Indium is easily oxidized and exhibits intriguing characteristics within the group III elements, especially as it forms many compounds by synthesis with group VI elements, such as In–O, , In–S, In–Se, and In–Te. , The formation of In–Se bonding is important in III–VI compounds, and it has been extensively studied and investigated for its derivatives in various applications. ,, The investigation of In–Se-based materials is driven by their potential utilization in various applications, including solar cells, , Li-ion batteries, and ionizing radiation detectors, due to their noteworthy physical features, such as optical and electrical properties . The materials of the In–Se system have also attracted considerable interest due to its intrinsic structural properties, including phase transition (transformation), multicrystalline zones consisting different phases, and structural imperfections. , Extensive research has been conducted on materials derived from the In–Se system, and numerous works have investigated the phase diagram of the In–Se system with different stoichiometry and different modifications. Previous investigations have reported that the presence of stable phases in this In–Se system includes the stoichiometric compositions of InSe, In 2 Se 3 , In 4 Se 3 ,…”
Section: Introductionmentioning
confidence: 99%
“…The Raman frequencies observed at approximately 114, 127, 142, and 196 cm –1 were identified as the A g modes, while those at 175 and 291 cm –1 were attributed to E 2g 1 and A 1g 2 , respectively. , The Raman peaks at 127 and 142 cm –1 , characteristic of h-GaTe, are distinctly observable . Simultaneously, Raman peaks at 115, 175, 196, and 291 cm –1 , corresponding to m-GaTe, are clearly evident as depicted in Figure a. These peaks consistently exhibited intensity variations with changes in the growth temperature. Notably, the Raman peak intensities corresponding to h-GaTe (127 and 142 cm –1 ) gradually decrease with increasing growth temperature, indicating the suppression of the h-GaTe phase in the film at higher growth temperatures.…”
Section: Resultsmentioning
confidence: 90%